Radiosensitivity and Induction of Apoptosis by High LET Carbon Ion Beam and Low LET Gamma Radiation: A Comparative Study. (15th June 2014) - Ghorai, Atanu; Bhattacharyya, Nitai P.; Sarma, Asitikantha; Ghosh, Utpal
Abstract : Cancer treatment with high LET heavy ion beam, especially, carbon ion beam ( 12 C), is becoming very popular over conventional radiotherapy like low LET gamma or X-ray. Combination of Poly(ADP-ribose) polymerase (PARP) inhibitor with xenotoxic drugs or conventional radiation (gamma or X-ray) is the newer approach for cancer therapy. The aim of our study was to compare the radiosensitivity and induction of apoptosis by high LET 12 C and low LET gamma radiation in HeLa and PARP-1 knocked down cells. We did comet assay to detect DNA breaks, clonogenic survival assay, and cell cycle analysis to measure recovery after DNA damage. We measured apoptotic parameters like nuclear fragmentation and caspase-3 activation. DNA damage, cell killing, and induction of apoptosis were significantly higher for 12 C than gamma radiation in HeLa. Cell killing and apoptosis were further elevated upon knocking down of PARP-1. Both 12 C and gamma induced G2 /M arrest although the 12 C had greater effect. Unlike the gamma, 12 C irradiation affects DNA replication as detected by S-phase delay in cell cycle analysis. So, we conclude that high LET 12 C has greater potential over low LET gamma radiation in killing cells and radiosensitization upon PARP-1 inhibition was several folds greater for 12 C than gamma.